Analysis of Follow up Audit - Lusiana Lusiana; Ali Djamhuri; Yeney Widya Prihatiningtias (Jurnal Economia, 2017)
Abstract: Analysis of Follow up Audit. This study aimed to explain the process of follow up audit in Sanggau local government by using management functions (planning, organizing, directing, and controlling) as the analysis instrument and identify problems that caused follow up audit was not optimal. This study used a qualitative approach with case study model and focused on OPD that still have unfinished findings. The selected informant is the Head of OPD; a technical official handling follows up audit and an Inspectorate official. The results of the study showed that there were some weaknesses in the process of follow up audit. For example, there was no specific policy about follow up audit, the slow responses of other parties in the process of coordination and the coordination between OPD and monitoring institution was not intensive; the leader was not able to give motivation, the low commitment of the leader, Difficulties in the evaluation process and the evaluation was not periodically, the role of TPTGR Assembly Consideration was not optimal, and the technical obstacles that was faced by OPD. Keyword: follow up audit, management function, planning, organizing, directing, controlling.Abstrak: Analisis Penyelesaian Tindak Lanjut Hasil Pemeriksaan. Penelitian ini bertujuan untuk menjelaskan proses penyelesaian Tindak Lanjut Hasil Pemeriksaan di Pemerintah Kabupaten Sanggau melalui pelaksanaan fungsi-fungsi manajemen (perencanaan, penggorganisasian, pengarahan, dan pengendalian) sebagai alat analisisnya, dan mengidentifikasi permasalahan yang menyebabkan belum optimalnya penyelesaian TLHP. Penelitian ini menggunakan pendekatan kualitatif dengan model studi kasus dan difokuskan pada Organisasi Perangkat Daerah (OPD) yang masih memiliki temuan yang belum tuntas. Informan yang dipilih, yaitu pimpinan OPD, salah satu pejabat teknis yang menangani TLHP dan salah satu pejabat Inspektorat daerah. Hasil penelitian menunjukkan terdapat kelemahan dalam proses penyelesaian TLHP yang menyebabkan penyelesaian TLHP belum optimal, yaitu belum tersedianya kebijakan khusus tentang TLHP; lambatnya respon pihak lain dalam proses koordinasi dan belum intensifnya koordinasi antara OPD dan lembaga pengawasan; pimpinan belum mampu memberikan motivasi; kurangnya komitmen pimpinan; kesulitan dalam melakukan proses evaluasi dan tidak dilaksanakan evaluasi secara berkala; belum optimalnya peran Majelis Pertimbangan TPTGR; dan kendala-kendala teknis yang dihadapi oleh OPD. Kata Kunci: TLHP, Fungsi Manajemen, Perencanaan, Pengorganisasian, Pengarahan, Pengendalian.